Restrictive Pulmonary Dysfunction May Increase Blood Loss During Liver Resection. Issue 12 (December 2021) - Yoshikawa, Takahiro; Hokuto, Daisuke; Yasuda, Satoshi; Kamitani, Naoki; Matsuo, Yasuko; Sho, Masayuki
Background: Restrictive pulmonary dysfunction (RPD) is a risk factor for perioperative complications during gastrointestinal surgery. We hypothesized that high airway pressure due to RPD results in increased intraoperative blood loss during liver surgery. Thus, we investigated the effects of RPD on perioperative outcomes for liver resection. Methods: This study included 496 patients who underwent curative liver resection at our hospital between April 2009 and April 2020. Perioperative outcomes for the RPD and control groups were compared. Restrictive pulmonary dysfunction was defined as % vital capacity <80%. Results: Forty-one patients (8.3%) had RPD. No significant differences were observed in intraoperative blood losses (440 mL vs 320 mL, P = .340), overall complication rates (29.3% vs 31.2%, P = .797), or pulmonary complication rates (4.9% vs 9.0%, P = .286) between the RPD and control groups. In the 256 patients who underwent anatomical liver resection, 18 patients (7.0%) had RPD. The intraoperative blood loss was significantly higher in the RPD group (925 mL vs 456 mL, P = .013), but no differences in the overall complication rates (44.4% vs 37.3%, P = .528) or pulmonary complication rates (11.1% vs 10.5%, P = .589) between the two groups were detected. A multivariate analysis showed that RPD was an independent risk factor for intraoperative blood loss ≥500 mL during anatomical liver resection (odds ratio 4.132; 95% confidence interval 1.135-15.045; P = .031). Discussion: Restrictive pulmonary dysfunction may be a risk factor for intraoperative blood loss during anatomical liver resection, which requires exposure of the main hepatic vein.